Time course of red cell volume and plasma volume over six months in compensated chronic heart failure. (5th January 2021) - Ahlgrim, Christoph; Seiler, Florian; Birkner, Philipp; Staudacher, Dawid Leander; Grundmann, Sebastian; Bode, Christoph; Pottgiesser, Torben
Abstract: Background: In patients with chronic heart failure (CHF), volume overload is usually described as an expansion of plasma volume (PV). Additional red cell volume (RCV) expansion also occurs in a relevant fraction of compensated CHF patients. So far, little is known about the stability of these vascular volumes and possible volume excess in compensated CHF patients over time. Methods and results: This study aims at quantification of blood volume and its components, RCV and PV (raw values and adjusted for sex and anthropometric characteristics, expressed as per cent of the expected normal value), using an abbreviated carbon monoxide (CO) rebreathing method (aCORM) in 14 patients (two women) with systolic CHF at baseline and at a follow‐up visit after approximately 6 months. While a vast heterogeneity was observed concerning RCV (82% to 134% of normalized alues) and PV (72% to 131% of normalized values), the vascular volumes showed a mean change of 1.2% and −1.3% after a mean follow‐up of 183 days. Conclusions: The vascular volumes including individual volume excess appear to be stable in compensated CHF patients. The reason for this individual volume response concerning both RCV and PV in CHF remains unclear and deserves further clarification.